2011
DOI: 10.14710/jitaa.36.1.55-60
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF INCLUSION CALCIUM-PALM FATTY ACID (Ca-PFA) ON GROWTH PERFORMANCE AND PROFILE OF BODY FATTY ACID OF BROILER

Abstract: A study of effect of inclusion of calcium-palm fatty acid (Ca-PFA) in the diets on growth performance and profile of body fatty acid has been conducted for 4 weeks in broiler. A total of 160 birds were used in present experiment which was arranged in a Completely Randomized Design with 4 treatments and 5 replications (8 birds each). Dietary inclusions of Ca-PFA of 0, 5, 10 and 15% were reflected as R0, R1, R2 and R3, respectively. Results of the experiment showed that growth performance based on the feed consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Research by [16] reported that giving Ca-PFAD in the ration up to 15% had no effect on LWG and carcasses of chickens. The addition of conjugated linoleate in feed can induce a rapid and significant decrease in fat accumulation and increase in protein deposition [21].…”
Section: Carcass Characteristics and Abdominal-fatmentioning
confidence: 98%
See 1 more Smart Citation
“…Research by [16] reported that giving Ca-PFAD in the ration up to 15% had no effect on LWG and carcasses of chickens. The addition of conjugated linoleate in feed can induce a rapid and significant decrease in fat accumulation and increase in protein deposition [21].…”
Section: Carcass Characteristics and Abdominal-fatmentioning
confidence: 98%
“…Medium chain fatty acids (MCFA) are more effectively absorbed and metabolized than saturated long chain fatty acids, and have antimicrobial properties in poultry [15]. The research results of [16] reported that the use of waste palm oil in poultry livestock can increase body weight and carcass weight compared to without adding palm fatty acids. Meanwhile, Anggreani et al [6] stated that the fatty acids in calcium soap can be used as an energy source for poultry feed to support improving carcass quality.…”
Section: Carcass Characteristics and Abdominal-fatmentioning
confidence: 99%
“…Besides, in some places, CaSPO are cheaper than conventional lipid sources used in formulations for broiler chickens. Dewi et al (2011) reported that 5% CaSPO in broiler chickens' diet increased feed intake, while the incorporation of 15% CaSPO reduced feed intake. However, the final live weight was not influenced by CasPO level in the diet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, calcium soaps of palm oil are much less expensive than conventional vegetable oils used in poultry diets. Dewi et al (2011) reported that with a 5% of calcium-palm oils in the diet, broiler chickens fed by four weeks showed increased feed intake, whereas those fed at 15% showed reduced feed intake; final body weight was unaffected by dietary level of calcium-palm fatty acid.…”
Section: Introductionmentioning
confidence: 99%